2018
DOI: 10.1080/07853890.2018.1489143
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of sauna bathing with inflammation and oxidative stress: the KIHD prospective cohort study

Abstract: Observational evidence supports the hypothesis that reduction in inflammation may be one of the pathways linking frequent sauna bathing with decreased risk of acute and chronic disease conditions. KEY MESSAGES Cross-sectional evidence or short-term studies suggest Finnish sauna bathing may exert its beneficial health effects via reduction in inflammation and oxidative stress; however, the long-term effects of sauna bathing on these outcomes are uncertain. In this population-based prospective cohort study, freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Evidence suggests that the responses produced by an ordinary sauna bath correspond to those produced by moderateor high-intensity physical activity such as walking. 32 Pathways implicated in the effects of sauna bathing on vascular disease and mortality risk include reduction in systemic BP 14 ; improvement in endothelial function [33][34][35] ; reduction in oxidative stress 36,37 and inflammation 38,39 ; beneficial modulation of the autonomic nervous system 11 ; positive alteration in levels of circulating vascular risk factors such as natriuretic peptides 40 and lipids 41,42 ; hormonal changes; improved arterial stiffness, arterial compliance, and intima media thickness 7,36,40,43,44 ; and improvement in the cardiorespiratory system 45 as well as cardiovascular function 3,4,46 (Figure 2). Indeed, these pathways are involved in the pathophysiology of chronic disease outcomes such as type 2 diabetes and CVD as well as mortality.…”
Section: Pathways Implicated In Health Benefits Of Sauna Bathingmentioning
confidence: 99%
“…Evidence suggests that the responses produced by an ordinary sauna bath correspond to those produced by moderateor high-intensity physical activity such as walking. 32 Pathways implicated in the effects of sauna bathing on vascular disease and mortality risk include reduction in systemic BP 14 ; improvement in endothelial function [33][34][35] ; reduction in oxidative stress 36,37 and inflammation 38,39 ; beneficial modulation of the autonomic nervous system 11 ; positive alteration in levels of circulating vascular risk factors such as natriuretic peptides 40 and lipids 41,42 ; hormonal changes; improved arterial stiffness, arterial compliance, and intima media thickness 7,36,40,43,44 ; and improvement in the cardiorespiratory system 45 as well as cardiovascular function 3,4,46 (Figure 2). Indeed, these pathways are involved in the pathophysiology of chronic disease outcomes such as type 2 diabetes and CVD as well as mortality.…”
Section: Pathways Implicated In Health Benefits Of Sauna Bathingmentioning
confidence: 99%
“…One study suggested that the lipid changes as a result of sauna exposure were similar to that produced by moderate-intensity physical exercise [37]. We have also previously shown that long-term sauna exposure is associated with reduction in levels of markers of inflammation [15, 16]. However, some of the mechanistic pathways implicated for the cardioprotective effects of sauna bathing did not appear to be consistent with our current findings, as we observed only minor changes due to a single sauna session.…”
Section: Discussionmentioning
confidence: 99%
“…The specific cardiovascular adaptations produced by long-term sauna bathing is not certain, but the effects of sauna bathing on cardiometabolic health outcomes have been linked to its beneficial impact on circulatory and cardiovascular function. Regular long-term sauna bathing has been shown to produce blood pressure lowering effects [14] as well as reducing levels of markers of inflammation [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…Rea reported that the use of sauna therapy improved the condition of patients with confirmed exposure to mold (including stachybortrys), those who had mycotoxins (including ochratoxin) in their urine, and patients who had impaired neurocognitive testing or autonomic nervous system testing results and whose conditions were refractory to other treatments. 4 In a review of the high prevalence of fatal dementia in Finland, 5 1 Our prospective studies have shown that higher frequency and duration of sauna bathing are related to a lower risk of cardiovascular mortality, sudden cardiac death, stroke, hypertension, pulmonary diseases, and dementia. [1][2][3] The feelings of relaxation and promotion of mental health and well-being associated with sauna sessions might be linked to the increased production of circulating levels of hormones such as endorphins.…”
mentioning
confidence: 99%
“…1 We have also reported an inverse association of frequency of sauna with several inflammatory markers, suggesting that the beneficial effect of sauna bathing on disease outcomes may in part be mediated via reduced inflammation. 4 The inverse associations between sauna bathing and adverse outcomes have persisted despite adjustments for socioeconomic status and physical activity, which are potential surrogate markers of healthy lifestyles.…”
mentioning
confidence: 99%